Pediatric Home Parenteral Nutrition in France: A six years national survey. Issue 10 (October 2021) - Goulet, Olivier; Breton, Anne; Coste, Marie-Edith; Dubern, Béatrice; Ecochard-Dugelay, Emmanuelle; Guimber, Dominique; Loras-Duclaux, Irène; Abi Nader, Elie; Marinier, Evelyne; Peretti, Noel; Lambe, Cecile
Summary: Background and aims: Home Parenteral Nutrition (HPN) is the cornerstone management for children suffering from chronic intestinal failure (CIF). In France, HPN is organized from a network of 7 certified centers located in University Hospitals spread across the national territory. This study aims to review the data involving children on HPN over a 6-years period in France to outline the global and continuous improvement in care. Patients and methods: This cross-sectional study included all children enrolled in any of the 7 French HPN certified centers from January 1st, 2014 to December 31st, 2019. Data was recorded from annual databases provided by each center regarding: age at inclusion, indication and duration of HPN, type of intravenous lipid emulsion (ILE), outcome [PN weaning off, transfer to adult center, death, intestinal transplantation (ITx)], rate of catheter-related bloodstream infections (CRSBIs) for 1000 days of HPN, Taurolidine lock procedure (TLP) use and prevalence of cholestasis defined as conjugated bilirubin ≥20 μmol/l. Results: The number of patients increased by 43.6% from 268 in 2014 to 385 in 2019. According to the year of follow up, the indications for HPN were short bowel syndrome (SBS) (42.3–46.6%), congenital enteropathies (CE) (18.5–22.8%), chronic intestinal pseudo-obstruction syndrome (CIPOS) (13.0–16.3%), long segment Hirschsprung's disease (LSHD) (9.7–13.3%), Crohn's disease (CD) (1.6–2.6%) and other non-primary digestive diseases (NPDD) such as immune deficiency, cancer or metabolic disease (4.0–9.2%). The median age at discharge on HPN decreased from 11.7 months in 2014 to 8.3 months in 2019 (p < .001). By December 31st, 2019, 44.8% of children had left the HPN program after a median duration ranging between 39.9 and 66.4 months. Among these patients, 192 (74.2%) were weaned off PN (94.7% SBS), 41 (15.8%) were transferred to adult centers for CIPOS (42%), SBS (31%) or CE (27%), 21 died (8.1%) – mostly in relation to cancer or immune deficiency – and 5 were transplanted (1.9%): 4 underwent combined liver-intestine transplantation for LSHD (n = 2), SBS, CE and one multivisceral Tx for CIPOS. The use of a composite fish-oil based ILE increased from 67.4% in 2014 to 88.3% in 2019 (p < 0.001). CRBSIs dropped from 1.04 CRSBIs per 1000 days HPN in 2014 to 0.61 in 2019 (p < 0.001) while meantime, the percentage of children receiving TLP increased from 29.4% to 63.0% (p < 0.001). The prevalence of cholestasis (conjugated bilirubin ≥ 20 μmol/l) was low and stable between 4.1 and 5.9% of children during the study period. Conclusion: In France, the number of children enrolled in a HPN program continuously increased over a 6 years period. SBS is the leading cause of CIF requiring HPN. The rate of CRBSIs dropped dramatically as the use of TLP increased. Mortality rate was low and mainly in relation to the underlying disease (cancer, immune deficiency). Cholestasis and intestinal Tx remained very rare.